Employable Wealth: Reframing Community Cultural Wealth as Employability for Students of Color in Higher Education - Burnett, Christopher; Taylor, Zachary (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2025)
Institutions of higher education have increased their focus on their students’ post-graduate outcomes, primarily these students’ ability to become successfully employed after graduation. Known as employability, many researchers have explored how postsecondary institutions do or do not prepare students for the world of work. However, many conceptions of employability do not adequately capture the lived experiences of students of Color, many of whom have been minoritized from the higher education system, and thus, do not access gainful post-graduate employment at the same level as their White peers. For this reason, we argue that traditional models and practices related to post-graduate employability in higher education must reframe ideologies surrounding employability, namely Yosso’s (2005) community cultural wealth model, which aligns nicely with and expands extant theoretical and conceptual frameworks. We then address directions forward and implications for policy and practice to support students of Color on their path toward post-graduate employment.